Global distribution of the terrestrial moisture dynamics response to the meteorological dry-wet abrupt alternation - Jianyu Fu; Mingzhu Cao; Yang Lu; Chunzhu Wei; Xuejin Tan; Meiling Zheng; Liqian Peng; Wenhao Jia; Bingjun Liu (Journal of Hydrology, 2026)

Spatiotemporal Profiling of Intratumoral Free Payload Distribution via MALDI Imaging Mass Spectrometry: Implications for Drug-to-Antibody Ratio Optimization in Antibody–Drug Conjugates - Tingting Cai; Ziyi Li; Qiaofang Yan; Guangcun Huang; Kaiying Jia; Xiaotong Chen; Junling Dun; Jinghua Zou; Meiling Tan; Yue Wu; Fan Wang (The AAPS Journal, 2026)

SREBP1-activated lipid metabolism drives ferroptosis and progression of clear cell renal cell carcinoma - Bao Wang; Junpeng Fu; Jian Qian; Yuang Wei; Meiling Bao; Haoqi Miao; Xinzhe Zhao; Kezheng Shao; Yuan Song; Ruoyun Tan; Jie Li; Pengfei Shao (Science China Life Sciences, 2026)

Characterization of a myoinhibitory peptide and its role in neuroimmune regulation in Litopenaeus vannamei during Vibrio harveyi infection - Yongxiong Huang; Meiling Huang; XuYan Tan; Zhiqiang Zhang; Jia Cai; Yishan Lu; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2026)

Tetrahydrocurcumin for Major Depressive Disorder with Therapeutic Potential and Mechanistic Insights from Clinical and Preclinical Studies - Ying Guo; Jianping Xie; Haiyun Luo; Yun Yuan; Fang Long; Jingyuan Meng; Hui Tan; Yuanping Li; Bibo Cai; Meiling Chen; Liyan Yang; Jingmei Zhong; et al. (Molecular Neurobiology, 2026)

Copper oxide nanoparticles disrupt lysosomal function and promote foam cell formation in RAW264.7 macrophages - Yilin Luo; Kun Zhang; Lejiao Mao; Meiling Tan; Xiaomei Dong; Na Li; Yuexing Zhou; Chengzhi Chen; Zhen Zou; Jun Zhang (Toxicology, 2025)

NIR-activated endoplasmic reticulum stress amplifier to regulate phagocytosis for macrophage-mediated cancer immunotherapy - Yaru Zhang; Wenyu Xie; Jiamin Luo; Rui Gao; Zhimin Gao; Xinyi Wang; Yongxin Huang; Chen Lin; Meiling Tan; Zhiyao Hou (Chemical Engineering Journal, 2025)

2D manganese-doped calcium carbonate nanosheets as activable MRI/US imaging Guided enhanced calcium influx for Boosted regulatory cell death - Mingya Tan; Linlin Huo; Jie Zeng; Shiqi Zhu; Jianfeng Bao; Mengke Fan; Jiangyang Li; Meiling Liu; Jiayi Zhao; Zhenghuan Zhao (Chemical Engineering Journal, 2025)

The role of HMGB2 in the immune response of Nile tilapia (Oreochromis niloticus) to streptococcal infection - Yuhang Dong; Zhiqiang Zhang; Yongxiong Huang; Xuyan Tan; Xing Li; Meiling Huang; Jiaming Feng; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

Correction to: Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)

Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)
Although the functions of programmed death-1 (PD-1) on αβ T cells have been extensively reported, a role for PD-1 in regulating γδT cell function is only beginning to emerge. Here, we investigated the phenotypic and functional characteristics of PD-1-expressing γδT cells, and the molecular mechanism was also explored in the Plasmodium yoelii nigeriensis ( P. yoelii NSM)-infected mice . Flow cytometry and single-cell RNA sequencing (scRNA-seq) were performed. An inverse agonist of RORα, SR3335, was used to investigate the role of RORα in regulating PD-1 + γδT cells. The results indicated that γδT cells continuously upregulated PD-1 expression during the infection period. Higher levels of CD94, IL-10, CX3CR1, and CD107a; and lower levels of CD25, CD69, and CD127 were found in PD-1 + γδT cells from infected mice than in PD-1 − γδT cells. Furthermore, GO enrichment analysis revealed that the marker genes in PD-1 + γδT cells were involved in autophagy and processes utilizing autophagic mechanisms. ScRNA-seq results showed that RORα was increased significantly in PD-1 + γδT cells. GSEA identified that RORα was mainly involved in the regulation of I-kappaB kinase/NF-κB signaling and the positive regulation of cytokine production. Consistent with this, PD-1-expressing γδT cells upregulated RORα following Plasmodium yoelii infection. Additionally, in vitro studies revealed that higher levels of p-p65 were found in PD-1 + γδT cells after treatment with a RORα selective synthetic inhibitor. Collectively, these data suggest that RORα-mediated attenuation of NF-κB signaling may be fundamental for PD-1-expressing γδT cells to modulate host immune responses in the spleen of Plasmodium yoelii nigeriensis –infected C57BL/6 mice, and it requires further investigation.

MnO2 nanozyme with lanthanide-based radiosensitization for advanced radiotherapy by tumor microenvironment triggering STING pathway activation - Meiling Tan; Zhimin Gao; Xiaozhao Wang; Chen Lin; Yuchi Wan; Wenyu Xie; Wei Chen; Yaru Zhang; Zewei Quan; Zhiyao Hou (Chemical Engineering Journal, 2024)

Dorsal and ventral fronto-amygdala networks underlie risky decision-making in age-related cognitive decline - Ping Ren; Manxiu Ma; Yuchuan Zhuang; Jiayin Huang; Meiling Tan; Donghui Wu; Guozhi Luo (GeroScience, 2023)
Older adults often have difficulty in making decisions under uncertainty, increasing the risk of financial exploitation. However, it is still under investigation about the extent to which cognitive decline influences risky decision-making and the underlying neural correlates. We hypothesized that the individual differences of risk-taking behavior depend on cognitive integrity, in which the dorsal and ventral fronto-amygdala connectivity would play dissociable roles. In the current study, thirty-six young and 51 older adults were tested with the Iowa gambling task combing resting-state and task-related functional magnetic resonance imaging. The results showed significant changes in behaviors and the fronto-amygdala network in older adults relative to young adults. More importantly, age-effect on risk-taking behaviors was remarkably different in cognitively normal and impaired older adults. In resting-state analysis, task performance was positively correlated with the ventral fronto-amygdala connectivity and negatively correlated with the dorsal fronto-amygdala connectivity in cognitively impaired older adults, compared with cognitively normal individuals. Furthermore, task-related analysis confirmed the relationships between dorsal/ventral fronto-amygdala network and risk-taking behaviors depending on cognitive integrity. These findings indicate that the fronto-amygdala network is crucial for understanding altered risky decision-making in aging, suggesting dissociable contributions of the dorsal and ventral pathways in the context of cognitive decline.

Design and synthesis of peptide-drug conjugates to double target EGFR - Xiaozhuo Tan; Meiling Le; Haiwen Wang; Bitao Huo; Tiantian Yu; Peng Huang; Tiangang Luan; Shijun Wen (Phytochemistry Letters, 2023)

Ambient air pollution and the health-related quality of life of older adults: Evidence from Shandong China - Jialong Tan; Nuo Chen; Jing Bai; Peizhe Yan; Xinyu Ma; Meiling Ren; Elizabeth Maitland; Stephen Nicholas; Wenjing Cheng; Xue Leng; Chen Chen; Jian Wang (Journal of Environmental Management, 2023)

Involvement of a receptor-like kinase complex of FvFLS2 and FvBAK1 in brassinosteroids-induced immunity in postharvest strawberry fruit - Chunhong Li; Kaituo Wang; Meiling Tan; Changyi Lei; Shifeng Cao (Postharvest Biology and Technology, 2023)

High-throughput sequencing reveals tuber mustard genes responsive to Plasmodiophora brassicae in the early stage of infection - Zhaoming Cai; Meiqin Xiang; Jing Tan; Chunhong Cheng; Ying Liu; Jiayu Shi; Meiling Shi; Jin Li; Diandong Wang (Physiological and Molecular Plant Pathology, 2023)

OsEXPA10 mediates the balance between growth and resistance to biotic stress in rice - Jiang Tan; Meiling Wang; Zhenying Shi; Xuexia Miao (Plant Cell Reports, 2018)

LIM-homeobox gene Lhx8 promote the differentiation of hippocampal newborn neurons into cholinergic neurons in vitro - Peipei Zhu; Haoming Li; Guohua Jin; Meiling Tian; Xuefeng Tan; Jinhong Shi; Linqing Zou; Jianbing Qin (In Vitro Cellular & Developmental Biology - Animal, 2013)

Lhx8 promote differentiation of hippocampal neural stem/progenitor cells into cholinergic neurons in vitro - Jinhong Shi; Haoming Li; Guohua Jin; Peipei Zhu; Meiling Tian; Jianbing Qin; Xuefeng Tan; Shuqing Zhao; Fuyu Wang; Yurong Hua; Yong Xiao (In Vitro Cellular & Developmental Biology - Animal, 2012)

Characterization and identification of Sox2+ radial glia cells derived from rat embryonic cerebral cortex - Haoming Li; Guohua Jin; Jianbing Qin; Meiling Tian; Jinhong Shi; Weiwei Yang; Xuefeng Tan; Xinhua Zhang; Linqing Zou (Histochemistry and Cell Biology, 2011)

Generation and identification of rat fetal cerebral radial glia-like cells in vitro - Haoming Li; Guohua Jin; Jianbing Qin; Meiling Tian; Xuefeng Tan; Xinhua Zhang; Weiwei Yang; Jinhong Shi; Linqing Zou (In Vitro Cellular & Developmental Biology - Animal, 2011)